Muslim Consumer Behavior Towards the Existence of Halal Brands on Ice Cream Products - Milzam, Muhammad; Veby, Az. Zahra Sherly; Rahmatika, Devi; Saputra, Arya Ajhie; Putri, Najwa Tiara Junaedi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article about Muslim consumer behavior is to learn more about the existence of a halal brand on the purchase of ice cream products. This literacy says that consumer behavior is important to influencing the existence of a halal brand. The lifestyle of Muslim consumers, which are concerned about whether they are buying or consuming a product, especially ice cream, is due to a tendency to care about religious teaching (Islam). This type of study is library research conducted through the way we study books and other data sources. The research method used is a qualitative study. The results of the study state that consumer behavior has a significant impact on existence of halal brands when purchasing Walls ice cream.